Health-related quality of life: a study among young adult cancer survivors - Ng, Jefferson Khai Qiang; Lai, Yong Guang (2019)
Along with the advancement of medical technologies, the prevalence of young adult cancer survivors in Malaysia is on the rise. However, less is known about the health-related quality of life (HRQOL) as perceived by these survivors over the course of their survivorship trajectory. This mixed methods research was to explore how variables were to influence the HRQOL of young adult cancer survivors in Malaysia. Pearson product-moment correlation test was conducted with the objective to examine the relationship between time since recovery and HRQOL of young survivors. Comparative statistical analysis such as one-way analysis of variance (ANOVA) and independent sample t-test were to determine the group differences of educational level and gender with HRQOL respectively. Semi-structured interviews enhanced the exploratory process of understanding perceived HRQOL of young survivors during their survivorship. Positive correlation, although not statistically significant, was found between time since recovery and HRQOL, while having tertiary education (except Doctorate degree) and the male gender were protective factors against low quality of life among young survivors. Interview findings revealed that physical dysfunctionality, social stigmatization, and inability returning to work were major sources of their HRQOL disturbance; however, the disturbances were encountered with perceived optimism and hopefulness. This research contributes a comprehensive baseline understanding of HRQOL among young Malaysian cancer survivors. As most researches were done among older adult cancer survivors or paediatric cancer survivors, this research raises greater awareness for the need of interventions tailored for this population in efforts to promote their well-being, and reducing cancer-related mortality.